Dla każdego z poniższych układów sprawdż czy podana obok para jest jego rozwiązaniem:

a) x+2y=9 x=1 y=4
3x-y =-1

b) 2x-5y=11 x=-2 y=-3
x+y=-6

c) 2x-4y=6 x=½ y=-½
x+y=0

d) 2x +y=1,5 X=0,4 y=0,7
x-y=0,3

e) x+y=3⁵/₆ x=1½ y=2¹/₃
y-x= ⁵/₆

f) x+y=3√2 x=5√2 y=-2√2
2x+5y=0

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-28T14:03:26+01:00
A) x+2y=9 x=1 y=4
3x-y =-1

x=9-2y
3x-y=-1

3(9-2y)-y=-1
27-6y-y=-1
-7y=-28 /-7
y=4

3x-4=-1
3x=3 /3
x=1

JEST!

b) 2x-5y=11 x=-2 y=-3
x+y=-6

2*(-2)-5*(-3)=-4+15=11
-2-3=-5
NIE JEST!
c) 2x-4y=6 x=½ y=-½
x+y=0

2*1/2-4*(-1/2)=6
1+2=3

1/2 - 1/2 =0
NIE JEST
d) 2x +y=1,5 X=0,4 y=0,7
x-y=0,3

2*0,4+0,7=1,5
0,8+0,7=1,5

0,4-0,7=-0,3
NIE JEST
e) x+y=3⁵/₆ x=1½ y=2¹/₃
y-x= ⁵/₆

1½+2¹/₃=3⁵/₆

2¹/₃-1½ =⁵/₆
JEST!

f) x+y=3√2 x=5√2 y=-2√2
2x+5y=0

5√2-2√2=3√2

2*(5√2)+5*(-2√2)=0
10√2-10√2=0

JEST!

2 3 2
2009-11-28T14:10:05+01:00
A) x+2y=9
3x-y =-1

x=9-2y
3(9-2y)-y=-1

x=9-2y
27-6y-y=-1

x=9-2y
-7y=-1-27

x=9-2y
-7y=-28 /:(-7)

x=9-2y
y=4

x=9-2*4
y=4

x=9-8
y=4

x=1
y=4

c)2x-4y=6
x+y=0

2x-4y=6
x= -y

2(-y)-4y=6
x= -y

-2y-4y=6
x= -y

-6y=6/:(-6)
x= -y

y= -1
x= -y

y=-1
x= -(-1)

y=-1
x=1

d)
2x +y=1,5
x-y=0,3

3x=1,8/:3
x=0,6

x-y=0,3
x=0,6

0,6-y=0,3
x=0,6

-y=0,3-0,6
x=0,6

-y=-0,3/*(-1)
x=0,6

y=0,3
y=0,6
















2 4 2